Bhamati and Vivaraṇa schools of Advaita Vedanta : a critical approach - Roodurmum, Pulasth Soobah (Motilal Banarsidass Publishers, 2002)
Study of Bhāmatī of Vācaspatimiśra, fl. 976-1000 and Pañcapadikāvivaraṇa of Prakāśātman, classical work on Advaita and Vedanta philosophy.